Evaluation of physical and chemical modifications to drug reservoirs for stimuli-responsive microneedles - Luchi Li; Qonita Kurnia Anjani; Aaron R. J. Hutton; Mingshan Li; Akmal Hidayat Bin Sabri; Lalitkumar Vora; Yara A. Naser; Yushi Tao; Helen O. McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2025)
Hydrogel-forming microneedle (MN) arrays are minimally-invasive devices that can penetrate the stratum corneum , the main barrier to topical drug application, without causing pain. However, drug delivery using hydrogel-forming MN arrays tends to be relatively slow compared to rapid drug delivery using conventional needles and syringes. Therefore, in this work, for the first time, different physical and chemical delivery enhancement methods were employed in combination with PVA-based hydrogel-forming MN arrays. Using a model drug, ibuprofen (IBU) sodium, the designed systems were assessed in terms of the extent of transdermal delivery. Iontophoresis (ITP) and heat-assisted drug delivery technology were investigated as physical permeation enhancement techniques. Ex vivo studies demonstrated that the ITP (0.5 mA/cm 2 )-mediated combination strategy significantly enhanced the transdermal permeation of IBU sodium over the first 6 h (~ 5.11 mg) when compared to MN alone (~ 1.63 mg) ( p < 0.05). In contrast, heat-assisted technology showed almost no promoting effect on transdermal delivery. Furthermore, IBU sodium-containing rapidly dissolving lyophilised and effervescent reservoirs, classified as chemical modification methods, were prepared. Both strategies achieved rapid and effective ex vivo IBU sodium permeation, equating to ~ 78% (30.66 mg) and ~ 71% (28.43 mg) from lyophilised and effervescent reservoirs, respectively. Moreover, in vivo pharmacokinetic studies showed that the IBU sodium plasma concentration within lyophilised and effervescent groups reached a maximum concentration (C max ) at 4 h (~ 282.15 µg/mL) and 6 h (~ 140.81 µg/mL), respectively. These strategies not only provided rapid achievement of therapeutic levels (10–15 µg/ml), but also resulted in sustained release of IBU sodium for at least 48 h, which could effectively reduce the frequency of administration, thereby improving patient compliance and reducing side effects of IBU sodium. Graphical Abstract

Prevalence of key resistance alleles associated with DMI and SDHI fungicide resistance in European Zymoseptoria tritici populations in 2022 - S. Kildea; T. Heick; F. Hutton; C. Bataille; L. Aldén; J. Kaneps; A. Mäe; S. Weigand; J. Zajc; A. S. Walker; P. Hellin (Journal of Plant Diseases and Protection, 2025)

The tomato gene Ty-6, encoding DNA polymerase delta subunit 1, confers broad resistance to Geminiviruses - Xuexue Shen; Upinder Gill; Marjon Arens; Zhe Yan; Yuling Bai; Samuel F. Hutton; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The tomato Ty-6 gene conferring resistance against begomoviruses has been cloned and shown to be a variant of DNA polymerase delta subunit 1. Abstract Ty-6 is a major resistance gene of tomato that provides resistance against monopartite and bipartite begomoviruses. The locus was previously mapped on chromosome 10, and in this study, we fine-mapped Ty-6 to a region of 47 kb, including four annotated candidate genes. Via whole-genome resequencing of Ty-6 breeding lines and several susceptible breeding lines, the polymorphisms in gene sequences were discovered and gene-associated markers were developed for marker-assistant breeding. Further, virus-induced gene silencing and candidate gene overexpressing in susceptible tomatoes revealed that Ty-6- mediated resistance is controlled by Solyc10g081250, encoding the DNA polymerase delta subunit 1, SlPOLD1 . The single nucleotide polymorphism of Ty-6 results in an amino acid change that might influence the fidelity of virus DNA replication.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Development and Evaluation of Dissolving Microarray Patches for Co-administered and Repeated Intradermal Delivery of Long-acting Rilpivirine and Cabotegravir Nanosuspensions for Paediatric HIV Antiretroviral Therapy - Kurtis Moffatt; Ismaiel A. Tekko; Lalitkumar Vora; Fabiana Volpe-Zanutto; Aaron R. J. Hutton; Jessica Mistilis; Courtney Jarrahian; Nima Akhavein; Andrew D. Weber; Helen O. McCarthy; Ryan F. Donnelly (Pharmaceutical Research, 2023)
Purpose Whilst significant progress has been made to defeat HIV infection, the efficacy of antiretroviral (ARV) therapy in the paediatric population is often hindered by poor adherence. Currently, two long-acting (LA) intramuscular injectable nanosuspensions of rilpivirine (RPV) and cabotegravir (CAB) are in clinical development for paediatric populations. However, administration requires access to healthcare resources, is painful, and can result in needle-stick injuries to the end user. To overcome these barriers, this proof-of-concept study was developed to evaluate the intradermal delivery of RPV LA and CAB LA via self-disabling dissolving microarray patches (MAPs). Methods Dissolving MAPs of two conformations, a conventional pyramidal and a bilayer design, were formulated, with various nanosuspensions of RPV and CAB incorporated within the respective MAP matrix. MAPs were mechanically robust and were capable of penetrating ex vivo skin with intradermal ARV deposition. Results In a single-dose in vivo study in rats, all ARV MAPs demonstrated sustained release profiles, with therapeutically relevant plasma concentrations of RPV and CAB detected to at least 63 and 28 d, respectively. In a multi-dose in vivo study, repeated MAP applications at 14-d intervals maintained therapeutically relevant plasma concentrations throughout the duration of the study. Conclusions These results illustrate the potential of the platform to repeatedly maintain plasma concentrations for RPV and CAB. As such, these MAPs could represent a viable option to improve adherence in the paediatric population, one that is capable of being painlessly administered in the comfort of the patient’s own home on a biweekly or less frequent basis. Graphical abstract

Designing a unique feedback mechanism for hydrogel-forming microneedle array patches: a concept study - Aaron R. J. Hutton; Melissa Kirkby; Eneko Larrañeta; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
Although microneedle array patch (MAP) technology is reaching ever closer to regulatory approval, it remains imperative that approaches to further improve patient acceptance are still explored. Addressing this perception, a water-filled reservoir was incorporated into a hydrogel-forming MAP system to provide a novel feedback mechanism. To confirm successful MAP skin insertion, the end user would both hear and feel the rupture of the water-filled reservoir. Interestingly, a 50-µL water-filled reservoir ruptured at 30.27 ± 0.39 N, which has previously been shown as the mean application force for MN insertion in human subjects following appropriate instruction. Importantly, no significant difference in % cumulative permeation of FITC-dextran 10 kDa and fluorescein sodium after 24 h was observed between a 50-µL reservoir and the current method of application that has been successfully used in both in vitro and in vivo studies ( p > 0.05). Therefore, as drug delivery was not affected, this proof-of-concept study has shown that a water-filled reservoir feedback mechanism has the potential to serve as a viable tool for consistent MAP skin insertion. Graphical abstract

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Characterization and elimination of linkage-drag associated with Fusarium wilt race 3 resistance genes - Jessica Chitwood-Brown; Gary E. Vallad; Tong Geon Lee; Samuel F. Hutton (Theoretical and Applied Genetics, 2021)
Key message Reducing the size of the I-3 introgression resulted in eliminating linkage-drag contributing to increased sensitivity to bacterial spot and reduced fruit size. The I-7 gene was determined to have no effect on bacterial spot or fruit size, and germplasm is now available with both the reduced I-3 introgression and I-7. Abstract Tomato ( Solanum lycopersicum ) production is increasingly threatened by Fusarium wilt race 3 ( Fol3 ) caused by the soilborne fungus, Fusarium oxysporum f. sp. lycopersici . Although host resistance based on the I-3 gene is the most effective management strategy, I-3 is associated with detrimental traits including reduced fruit size and increased bacterial spot sensitivity. Previous research demonstrated the association with bacterial spot is not due to the I-3 gene, itself, and we hypothesize that reducing the size of the I-3 introgression will remedy this association. Cultivars with I-7 , an additional Fol3 resistance gene, are available but are not widely used commercially, and it is unclear whether I-7 also has negative horticultural associations. To characterize the effect of I-3 on fruit size, segregating populations were developed and evaluated, revealing that the large I-3 introgression decreased fruit size by approximately 21%. We reduced the I-3 introgression from 5 to 140 kb through successive recombinant screening and crossing efforts. The reduced I-3 introgression and I-7 were then separately backcrossed into elite Florida breeding lines and evaluated for effects on bacterial spot sensitivity and fruit size across multiple seasons. The reduced I-3 introgression resulted in significantly less bacterial spot and larger fruit size than the large introgression, and it had no effect on these horticultural characteristics compared with Fol3 susceptibility. I-7 was also found to have no effect on these traits compared to Fol3 susceptibility. Together, these efforts support the development of superior Fol3 -resistant cultivars and more durable resistance against this pathogen.

Microneedle Mediated Transdermal Delivery of Protein, Peptide and Antibody Based Therapeutics: Current Status and Future Considerations - Melissa Kirkby; Aaron R.J. Hutton; Ryan F. Donnelly (Pharmaceutical Research, 2020)
The success of protein, peptide and antibody based therapies is evident - the biopharmaceuticals market is predicted to reach $388 billion by 2024 [1], and more than half of the current top 20 blockbuster drugs are biopharmaceuticals. However, the intrinsic properties of biopharmaceuticals has restricted the routes available for successful drug delivery. While providing 100% bioavailability, the intravenous route is often associated with pain and needle phobia from a patient perspective, which may translate as a reluctance to receive necessary treatment. Several non-invasive strategies have since emerged to overcome these limitations. One such strategy involves the use of microneedles (MNs), which are able to painlessly penetrate the stratum corneum barrier to dramatically increase transdermal drug delivery of numerous drugs. This review reports the wealth of studies that aim to enhance transdermal delivery of biopharmaceutics using MNs. The true potential of MNs as a drug delivery device for biopharmaceuticals will not only rely on acceptance from prescribers, patients and the regulatory authorities, but the ability to upscale MN manufacture in a cost-effective manner and the long term safety of MN application. Thus, the current barriers to clinical translation of MNs, and how these barriers may be overcome are also discussed.

Ty-6, a major begomovirus resistance gene on chromosome 10, is effective against Tomato yellow leaf curl virus and Tomato mottle virus - Upinder Gill; John W. Scott; Reza Shekasteband; Eben Ogundiwin; Cees Schuit; David M. Francis; Sung-Chur Sim; Hugh Smith; Samuel F. Hutton (Theoretical and Applied Genetics, 2019)

Linkage between the I-3 gene for resistance to Fusarium wilt race 3 and increased sensitivity to bacterial spot in tomato - Jian Li; Jessica Chitwood; Naama Menda; Lukas Mueller; Samuel F. Hutton (Theoretical and Applied Genetics, 2018)

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Estrogen, progesterone, and HER2/neu receptor discordance between primary and metastatic breast tumours—a review - C. Yeung; J. Hilton; M. Clemons; S. Mazzarello; B. Hutton; F. Haggar; C. L. Addison; I. Kuchuk; X. Zhu; K. Gelmon; A. Arnaout (Cancer and Metastasis Reviews, 2016)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Identification of QTL associated with resistance to bacterial spot race T4 in tomato - Samuel F. Hutton; Jay W. Scott; Wencai Yang; Sung-Chur Sim; David M. Francis; Jeffrey B. Jones (Theoretical and Applied Genetics, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Ontogenetic expression of chromogranin A and its derived peptides, WE-14 and pancreastatin, in the rat neuroendocrine system - Sharon C. Barkatullah; W. J. Curry; Colin F. Johnston; John C. Hutton; Keith D. Buchanan (Histochemistry and Cell Biology, 1997)